Rapid Penang travel planner mobile application using GPS positioning and decision-making algorithm / Naslyiana Abdul Latif - Abdul Latif, Naslyiana (2015)
Penang is the place for tourist attraction. Thus, the public transportation system itself should be friendly user. Information about bus schedules and point of interest should be easy receive by users. Thus, this project will describe about Rapid Penang travel planner that implement in mobile application to make user easy get information regarding Rapid Penang services. The technique used by this project are GPS positioning and decision-making algorithm. GPS Positioning used for searching nearby location (station) whereas decision making algorithm used for making a decision by provide result on bus recommended, fares and routes. The method used to implement this project is Rapid Application Development (RAD). This application have been tested to 25 respondents. 22 respondents are local pedestrians and 3 respondents are outside traveler. The results shown that 88% respondents prefer to find information about Rapid Penang services using this application while 12% respondents do not agreed. This shows that majority of the respondents agreed with the application because all related information can be received easily and more efficient. Besides, user can find their current location without having to search it manually. Moreover, user can also plan their journey and get ideas on point of interest in Penang. On the other hand, there are minor respondents that do not agreed with this application. This is because they only used the bus services in a few times and for the same destination every day. Thus, to improve this application for future work, some element should be improve such as the covered area and zone should be more comprehensive, no internet connection in getting current location and road navigation on maps. In conclusion, this application proves that it is efficient and gives more benefit for user.